Les jardins alpino-japonais, histoire d’une possible utopie paysagère - Romain Billon (Projets de Paysage)
The aim of this article is to give an initial overview of the Japanese Alpine gardens created in France and Belgium by offering a historical study of the circumstances that led to their creation at the beginning of the 20th century, ranging from the interest in Japanese gardens which were discovered at the Universal Exhibitions at the end of the 19th century, to the interest in Alpine gardens inspired by English gardens and their decorative rockeries. By highlighting this style of gardening, now forgotten in the history of horticulture, we seek to understand why only a small number of amateurs—such as Albert Kahn and Ernest Van den Broeck—and professionals—such as Eugène Laumonnier and Charles Weiss—attempted to combine the two main styles of Japanese and Alpine gardens. To support this work, we adopted a theoretical approach based on an in-depth study of horticultural magazines and books of the period, combined with a practical approach developed from our professional experience as gardeners. Finally, we put forward hypotheses that could explain the disappearance of these gardens since the 1930s and question the relevance of reconstructing or restoring them.